2018
DOI: 10.9758/cpn.2018.16.1.422
|View full text |Cite
|
Sign up to set email alerts
|

From Gut to Brain: Alteration in Inflammation Markers in the Brain of Dextran Sodium Sulfate-induced Colitis Model Mice

Abstract: Objective: Neuropsychiatric manifestations like depression and cognitive dysfunction commonly occur in inflammatory bowel disease (IBD). In the context of the brain-gut axis model, colitis can lead to alteration of brain function in a bottom-up manner. Here, the changes in the response of the hypothalamic-pituitary-adrenal axis and inflammationrelated markers in the brain in colitis were studied. Methods: Dextran sodium sulfate (DSS) was used to generate a mouse model of colitis. Mice were treated with DSS for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Although IBD is a kind of gastrointestinal disease, characterized by chronic intestinal inflammation, dysregulated immune responses to intestinal microbiota, and dysfunction of the epithelial barrier [6], several studies have shown the presence of neuropsychiatric manifestations, such as depression and cognitive dysfunction, particularly during the active stage of the disease [7][8][9][10]. In a previous study, we also observed that DSS-induced colitis was accompanied with anxiety behavior [11].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although IBD is a kind of gastrointestinal disease, characterized by chronic intestinal inflammation, dysregulated immune responses to intestinal microbiota, and dysfunction of the epithelial barrier [6], several studies have shown the presence of neuropsychiatric manifestations, such as depression and cognitive dysfunction, particularly during the active stage of the disease [7][8][9][10]. In a previous study, we also observed that DSS-induced colitis was accompanied with anxiety behavior [11].…”
Section: Introductionmentioning
confidence: 69%
“…Similarly, in pathological conditions, such as IBD and PD, the dysregulation of norepinephrine, epinephrine, dopamine, and serotonin neurotransmitters levels can lead to a variety of gastrointestinal symptoms [15]. Also, rats with colitis showed increased hippocampal excitability and cortical inflammation [7,14,16]. In acute DSS-induced colitis mice, the expression of IL-6, TNF-α elevated, and microglia was activated in the brain tissue.…”
Section: Introductionmentioning
confidence: 99%
“…16 However, the possible physiological links between depression and IBD remain unclear. 17 Stress as a comorbid factor in both IBD and depression render the hypothalamus a possible mediator of IBD.…”
Section: Q11mentioning
confidence: 99%
“…Among these, the hippocampus is a key brain region within the limbic system that has been linked to depression in both humans and rodents (Dantzer et al., 2008), and during depressive states, there is a dysregulation of several neurotransmitter systems such as the serotonergic, noradrenergic, and GABAergic systems. mRNA levels of specific inflammatory markers, such as for COX-2, are upregulated in the hippocampus of mice with visceral inflammation (Do and Woo, 2018), and prolonged pharmacologically induced visceral inflammation gives rise to reduced hippocampal neurogenesis (Zonis et al., 2015). In addition, there is an inflammatory component to depression, as evident from alterations of interleukin 1 beta (IL-1ÎČ) and tumor necrosis factor alpha (TNF-α) levels in the limbic system of patients with depression (Hodes et al., 2015).…”
Section: Introductionmentioning
confidence: 99%